NEW TECHNOLOGICAL APPROACH FOR TREATMENT OF KARAKUL HIDES (American Journal of Technology and Applied Sciences, 2023)
This article discusses a new technological approach in the processing of karakul hides and comparing it with the traditional method. The results of chemical analysis and IR spectroscopy of hides processed by the studied method are presented, as well as the advantage of this method.